Philometra cephalus (Nematoda) infection in the gonads of the long-arm mullet Valamugil cunnesius : host-parasite relation - Radhakrishnan, S; Magitha, Beevi; Deepthi, G R; Treesa, Radhakrishnan (Indian Journal of Fisheries, 2016)
The long-arm mullet, Valamugil cunnesius (Val.) harbours an infection in their gonads, by the dracunculid nematode, Philometra cephalus Ramachandran. Though P. cephalus was reported from Mugil cephalus way back in 1975 and the parasite was reported to cause serious harm to the gonads of its host, so far no attempt has been made to study its nature of infection. This paper reports the results of the study on the host-parasite relation of P. cephalus. P. cephalus is highly host-specific and it infects both testis and ovary of V. cunnesius. The prevalence of infection was 41.7%; it was much higher in females (48.3%) than in males (28.2%). Prevalence registered an increasing trend with length of fish and advancing gonad maturity. Though hepato-somatic index, gonado-somatic index and condition factor were adversely affected by the infection, the greatest impact of the infection was on the fecundity, which was significantly lowered, by nearly four times, in the infected fish (mean fecundity = 13.8 x 103) compared to the uninfected fish (mean fecundity = 52.1 x 103). The high prevalence of the infection in females and the significant reduction in fecundity together could have serious adverse effects on the host population.